Menstrual health and hygiene among Indigenous Australian girls and women: barriers and opportunities - Emily Krusz; Nina Hall; Dani J. Barrington; Sandra Creamer; Wendy Anders; Minnie King; Helen Martin; Julie Hennegan (BMC, 2019)
Abstract Health inequities inhibit global development and achievement of the Sustainable Development Goals. One gendered health area, Menstrual Health & Hygiene (MHH), has received increasing attention in Low- and Middle-Income Countries as a barrier to health, wellbeing, and gender equity. Recent anecdotal evidence in Australia highlights that MHH also present challenges to High Income Countries, particularly among underrepresented populations, such as Indigenous Australian peoples, people from low socio-economic backgrounds, or communities that are remotely located. In this article, we chart the emergence of attention to MHH in the Australian context and highlight key considerations for the conduct of research with Aboriginal and Torres Strait Islander Peoples within the culturally- and gender-sensitive area of MHH. Further we draw on insights offered by a partnership between female Aboriginal and Torres Strait Islander leaders, NGO stakeholders, and non-Indigenous researchers. Through a convening (yarning circle) held in March 2018, the group identified multiple socioecological considerations for MHH research and practice, including: affordability and access to menstrual products, barriers to knowledge and culturally sensitive education, infrastructure and supply chain challenges, and the necessity of Indigenous-led research and community-driven data collection methods in addressing the sensitive topic. We draw together these insights to develop recommendations for future research, advocacy, and action in Australia.